Lupus anticoagulant hypoprothrombinemia syndrome associated with a hemorrhagic ovarian cyst in a girl with systemic lupus erythematosus : a case report - Min Hwa Son; Hyung Eun Yim (Korean Society of Pediatric Nephrology, 2024)
Lupus anticoagulant hypoprothrombinemia syndrome (LAHPS) is a rare entity characterized by the presence of lupus anticoagulant (LA) and prothrombin (factor II) deficiency. It may cause severe bleeding contrary to classical antiphospholipid syndrome. Here, we report a case of LAHPS presenting with a hemorrhagic ovarian cyst in a 17-year-old girl with systemic lupus erythematosus (SLE) nephritis. She had been followed up for 8 years. Her first manifestation of SLE was prolonged gingival bleeding after tooth extraction at 9 years of age. During the follow-up period, she had neither severe bleeding nor thrombotic complications despite a positive LA and a prolonged activated partial thromboplastin time (aPTT). At this visit, the patient presented with colicky abdominal pain, a hemorrhagic ovarian cyst, a prolonged prothrombin time, a prolonged aPTT, a low factor II level, and a positive LA, leading to the diagnosis of LAHPS. While a hemorrhagic ovarian cyst resolved completely in 3 months, she received oral pill, transfusions of red blood cells and plasma, and intravenous cyclophosphamide pulse therapy in combination with glucocorticoids due to persistent menorrhagia, anemia, prolonged aPTT, and lupus flaring. Thus, LAHPS needs to be considered in SLE patients with positive LA and prolonged aPTT.